Literature Prescribing Literature: Metaliterary Representations and Reflections in the Works of La Marchesa Colombi (1840–1920) - Sturli, Aurora (Quaderni d'Italianistica)

(untitled) (Iter Press, 2025)
In late nineteenth-century literature, the figure of the female reader held significant importance, both in literary representations and in cultural debate, and was closely connected to the discourse on literary identification. An analysis of the production of La Marchesa Colombi (Maria Antonietta Torriani) reveals that the author engaged with the theme in various ways. She overturned this literary topos through the representation of male readers who succumb to romantic fantasies, but she also depicted the dangers for young women of an insufficient sentimental education. With Torriani’s female characters, the act of reading is strongly attached to the type of education they received, and so it has practical implications in their lives, particularly relating to their marital status. For this reason, we can observe both negative and positive examples in Torriani’s works. And by comparing Torriani’s fictional works with her 1871 essay on women’s education and with paratexts in her production, we notice how the act of reading, according to Torriani, was a necessary part of women’s cultural and social formation.